Flipped Classroom Strategies and Self-Efficacy of Elementary Education Students - Luna, Sheena Kae (Journal of Interdisciplinary Perspectives, 2025)
Despite the global shift toward student-centered instruction, localized evidence on the impact of flipped classroom strategies on self-efficacy among elementary education students in Philippine higher education remains limited. Addressing this gap, the study examined the relationship between specific flipped classroom strategies and self-efficacy among Elementary Education students at Visayas State University Isabel Campus. Guided by Bandura’s Social Cognitive Theory, the study framed flipped instruction as a potential catalyst for enhancing teacher preparedness and confidence. Using a descriptive-correlational design, data were collected from 120 BEEd students through a validated survey instrument and analyzed using SPSS v29. Statistical tools included descriptive statistics (means and standard deviations), Pearson’s correlation, and multiple linear regression analysis. Results revealed that demonstration teaching (M = 3.85, SD = 0.36) and discussion-oriented strategies (M = 3.63, SD = 0.52) were the most frequently used. Students reported moderately high levels of self-efficacy across mastery experiences (M = 3.00), social modeling (M = 3.29), social persuasions (M = 2.82), and psychological responses (M = 2.89). Significant positive correlations were found between giving of course materials and all four self-efficacy dimensions (r = 0.49, p < 0.001 for social modeling), as well as between class reporting and key self-efficacy domains (r = 0.43, p < 0.001 for social modeling). Regression analysis identified giving of course materials (β = 0.42, t = 5.26, p < 0.001) and its combination with class reporting (β = 0.30, p = 0.001; β = 0.26, p = 0.005) as significant predictors of self-efficacy. These findings underscore the importance of integrating structured and participatory flipped strategies in teacher education programs to promote student engagement, independent learning, and confidence, ultimately supporting the development of competent and self-efficacious future educators.